Criteria of Risk Distribution in Contractual Obligations - ANTONOVA, Natalia A.; LUNYOVA, Elena N. (Journal of Advanced Research in Law and Economics, 2018)
One of the topical issues of civil law is risk distribution in contractual obligation, as in the process of execution of a contract there may arise the circumstances that – against the parties’ will – cause violation of the obligation and make execution of the contract impossible or very difficult. Thus, there’s a necessity for common criteria of distribution of contractual risks that allow preventing the appearance of unfavorable consequences or compensating them with less cost. These criteria could be called criteria of economic expedience.